Increasing Student Learning Interest through Project Based Learning (PjBL) Learning Model Assisted by Material Props Build Class V Student Room SDN Kesambi in 3 Cirebon - Refiana, Rena; Nurkholis; Sugesti, Ikariya; Indriasari, Venny (Annpublisher, 2023)
The background of this research is the low interest of students in learning mathematics. Can using the PjBL model assisted by teaching aids increase students' interest in learning mathematics in class V SDN Kesambi Dalam 3? The purpose of this study was to find out the benefits of the visual aid-assisted Pjbl model in attracting student interest in learning to improve mathematics learning. The type of research used is classroom action research (CAR), which consists of cycle I and cycle II. Each cycle consists of planning, implementing actions, observing and reflecting. This research was conducted at SDN Kesambi Dalam 3 with research subjects in class V with a total of 24 students. Data collection techniques were carried out through observation sheets which were analyzed descriptively using percentage techniques and questionnaires were analyzed using a Likert scale scoring system. Based on the results of the research that has been done, it can be concluded through the following matters: (1) In the first cycle, it was found that the student's learning interest reached 49,6 % which indicated that the student's interest category was not good (2) In the second cycle, it was found that the student's interest in learning students experienced an increase, namely 73.3% (3) Analysis of student interest in learning showed that the category of student interest in the learning process was good. Thus learning mathematics through the Pjbl model with props can increase students' interest in learning in class V SDN Kesambi Dalam 3 Cirebon.